Removable prosthodontics at a glance - Field, James, 1979-; Storey, Claire (Hoboken, NJ : Wiley Blackwell, 2020)
'Removable Prosthodontics at a Glance provides a comprehensive and accessible guide to the practical elements of complete and partial denture provision. It serves as the perfect illustrated guide for learners, and a handy revision guide for subsequent undergraduate and postgraduate studies. Following the familiar, easy to use at a Glance format, each topic is presented as a double page spread with text accompanied by clear colour diagrams and clinical photographs to support conceptual understanding. Key concepts such as patient assessment, material handling, denture design, making impressions, and much more are explained and superbly illustrated enabling the reader to visualise the intended clinical endpoint. Removable Prosthodontics at a Glance is a valuable resource for students studying dentistry and clinical dental technology, and those preparing for further studies in Prosthodontics'--
The function of removable prostheses -- Stability and retention -- Patient assessment for complete dentures -- Edentulous ridge presentations -- Patient assessment for partial dentures -- Factors complicating success -- Accessibility and operator position -- Pre-prosthetic treatment -- Revisiting the anatomy -- Making a primary impression -- completes -- Making a primary impression -- partials -- Special trays -- Compound & putty materials -- handling & manipulation -- Recording an upper functional impression -- Recording a lower functional impression -- Managing fibrous ridges -- Denture bases -- Recording the maxillo-mandibular relationship -- Prescribing the upper wax contour -- Prescribing the lower wax contour -- Tooth selection and arrangement -- Occlusal dimensions & occlusal schemes -- Respecting the neutral zone -- Assessing trial prostheses -- Fitting and reviewing finished prostheses -- Copying features from existing prostheses -- Classifying partial prostheses and material choices -- Designing partial prostheses -- Saddles, rests and clasps -- Connectors and bracing -- Surveying and preparing guide planes -- Designing frameworks -- case examples -- Precision attachments -- the fixed-removable interface -- Dealing with frameworks and substructures -- Altered cast technique and RPI system -- Swing-lock prostheses -- Gingival veneers -- Immediate and training prostheses -- Occlusal splints -- Implant-supported mandibular overdentures -- Principles of restoring maxillary defects -- Tissue conditioners, liners and re-basing -- Maintaining adequate oral hygiene -- Troubleshooting loose or painful dentures -- Gagging, other difficulties and making a referral -- Flow diagrams of procedural stages.
Includes bibliographical references and index.
Keywords: Denture, Complete; Denture, Partial, Removable; Handbook